PENGARUH PARTISIPASI ANGGOTA DAN PELAYANAN TERHADAP PENINGKATAN KOPERASI DI KOTA PALEMBANG - yunidar Erlina (JURNAL KOMPETITIF, 2015)
This research activity plan with the title Influence Member Participation and Client Service Improvement Cooperative in Palembang city has a long-term goal of the cooperative is expected to have the ability to increase the potential of innovative services or introduce the types of cooperatives in innovation and take advantage of new technologies into the economy and see forward and dare to take risks. Cooperative is an attempt to improve the welfare of members, therefore the service factor was instrumental in motivating members to participate in a cooperative effort to increase the amount of innovation and creativity that will benefit the business and at the same time improving the welfare of the People.By using primary data and secondary data is to support the achievement of these goals. Primary data were collected by distributing questionnaires to the respondents made in the sample. In this study, used field research is the data collection techniques performed by providing a set of questions or statements in writing to the respondent to answer. Questionnaires conducted by the respondents who are the sample to fill out questionnaires are complete and intact so the results of this research can be fit with what is expected.From this insturmen questionnaire created by five indicators, in the first trial to some respondents then tested the validity and reliability to be a valid and reliable questionnaire. Once the data is collected data will be analyzed to determine how the effect of taking a participation of members and services to increase the number of cooperatives by using Multiple Regression Analysis, Test-T, Test-F, Determination Test and Test of Hypothesis, selanjunya will be able to a conclusion.Ã‚Â Keywords : Participation, Service, Increase